Workplace Friendship and Teacher Citizenship Behaviour, The Moderating Role of Workplace Jealousy: An Empirical Analysis of Senior High Schools in Ghana - Mohammed Kamil Naail; Saeed Mohammed Owusu; Mariama Zakari; Samuel Awuni Azinga (Indonesian Management and Accounting Research, 2021)
The present study examines the effect of workplace friendship on teacher citizenship behaviour, moderated by workplace jealousy among senior high schools in Ghana. The study employs a quantitative research approach, whereby 384 respondents were sampled from among 22 public owned institutions in the Kumasi metropolis, using a simple random sampling technique. Employing Multiple Linear Regression Analysis, the surveyed data was analysed using SPSS version 23.0. All three (3) hypotheses in this study were supported. In particular, the study found that workplace friendship has a significant and positive effect on teacher citizenship behaviour; workplace jealousy has a significant and positive effect of teacher citizenship behavior; and workplace friendship interacting with workplace jealousy has a significant but very weak effect on teacher citizenship behaviour. It can be noted that, hypotheses two (2) of this study which is positively and significantly supported, seem different from that of previous studies with data from different countries. The perception of workplace jealousy from the Ghanaian context is perceived positive and quite different from that of other countries due to differences in historical and cultural backgrounds. Higher education institutions may derive enormous benefits from the findings of this study. Several implications to theory and practice were discussed.